Online Project Processing Information System at the Foundation Sumatran Orangutan Lestari - Fathur Muhammad Rahman; Muhammad Irwan Padli (Sistemasi: Jurnal Sistem Informasi, 2023)
The Online Project Processing Information System at the Sumatra Lestari Orangutan Foundation (YOSL-OIC) is of course website-based, which is a project report information system that is carried out online that allows users to access data in real-time and can make the right decisions in a short time and it also makes it easier for the industry to manage and work on projects in a planned, controlled, analytical and sustainable manner. Industry must also be able to control how project activities are carried out. At YOSL-OIC, Data processing information systems are being evaluated in a semi-manual fashion, which is inefficient in terms of both time and accuracy. The study's overarching goal is to create a web-based data system that streamlines data collecting and processing and can be accessed from any location, among other benefits. The application that is formed includes work data that shows features such as collecting pictures and videos during activities, lists of donors, and can input projects through the website directly without going through software such as Ms.Word or other Office parts and several others. Employees may quickly and easily save enormous volumes of data, generate comprehensive reports, and guarantee the safety of sensitive project information with the help of this program.